Towards a reading of the Peruvian Traditions from the theory of political representation - Sánchez Martínez, César Félix (2023)
In this article an interpretation of the Independence and State-Building processes in the Latin American Republics will be explored in line with Political Representation Theories exposed by Guerra, Furet and Cochin. Also, the use of Tradiciones Peruanas as a rich material to understand this process in Peru will be proposed through the analysis of a Palmean tradition referred to suffrage, the most important way of constructing legitimacy in Modern representation. Keywords: Political Representation Theories, Tradiciones peruanas, Ricardo Palma, Republican Peru, Wars of Independence